Islamic Religious Education as a Guideline for Self-Protection from Social Media Standard Pressures among Junior High School Adolescents - Maulidah, Sakhat; Untung, Slamet (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Social media has now transformed into a digital public space that not only presents information and entertainment, but has also become an arena of invisible competition. Within it, scattered standards of achievement, lifestyle, and physical appearance form false perceptions about ideal life. The purpose of this research is to describe and analyze how Islamic values taught in Islamic Religious Education can serve as guidelines for self-protection in facing psychological pressures caused by social media standards among junior high school students. The method used is field research conducted at a junior high school with a qualitative approach that is descriptive-analytical in nature. The primary data sources are Islamic Religious Education teachers and 9th-grade students, while the secondary data sources consist of homeroom teachers and relevant journal articles. Data collection techniques include interviews, observations, and documentation. The data analysis techniques involve data condensation, data display, and conclusion drawing and verification. The results of this research show that social media brings significant impact on the mental health and spirituality of adolescents. This is reinforced by the opinions of Islamic Religious Education teachers and homeroom teachers, who assess that today's teenagers are more bound to the digital world than to transcendental relationships with God. To address this issue, Islamic Religious Education values such as tauhid, iffah, and tawazun have proven effective as guidelines for protecting oneself from social media pressures. These three values build spiritual awareness, self-control, and balance in living digital life. Keywords:, Islamic Religious Education, Junior High School Students, Self-Protection, Social Media Standards.